2017
DOI: 10.2169/internalmedicine.56.7115
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty Liver Disease Is a Risk Factor for Type 2 Diabetes in Middle-aged Japanese Men and Women

Abstract: Objective Emerging studies have focused on the association between non-alcoholic fatty liver disease (NAFLD) and the risk of type 2 diabetes mellitus (T2DM). We aimed to investigate whether NAFLD diagnosed by ultrasonography could predict the risk of future T2DM in a Japanese middle-aged health check population.Methods We conducted a 10-year observational study in a health checkup population of middle-aged Japanese men and women at Hidaka Hospital from 2004 to 2013. We excluded cases with an alcohol intake exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
(31 reference statements)
0
20
1
1
Order By: Relevance
“…In addition, we previously reported that non-overweight with NAFLD has higher risk of incident diabetes than overweight/obesity without NAFLD [24]. Moreover, recent studies revealed that metabolic syndrome individuals with NAFLD have higher risk of incident diabetes than those without NAFLD [25,26]. These studies showed that NAFLD would be a major risk factor for incident type 2 diabetes than overweight/obesity.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we previously reported that non-overweight with NAFLD has higher risk of incident diabetes than overweight/obesity without NAFLD [24]. Moreover, recent studies revealed that metabolic syndrome individuals with NAFLD have higher risk of incident diabetes than those without NAFLD [25,26]. These studies showed that NAFLD would be a major risk factor for incident type 2 diabetes than overweight/obesity.…”
Section: Discussionmentioning
confidence: 90%
“…Obesity increases the risk of heart disease, type 2 diabetes, high blood pressure, and nonalcoholic fatty liver diseases . Obesity‐inducible HFD increases fat‐favorable Firmicutes and Proteobacteria populations and reduces the Bacteriodetes population in the gut microbiota of humans and mice .…”
Section: Discussionmentioning
confidence: 99%
“…The association between NAFLD and Type 2 diabetes is strong; an individual's risk of developing diabetes increases up to fivefold if they have a diagnosis of NAFLD . Currently, we are unable to predict which individuals with NAFLD will subsequently develop diabetes; therefore, joint European hepatology, diabetes and obesity guidelines advocate regular screening for diabetes in those with NAFLD using HbA 1c or oral glucose tolerance testing .…”
Section: Discussionmentioning
confidence: 99%